PREVENTIVE APPROACHES TO HEALTH RISKS FROM ENDOCRINE-DISRUPTING CHEMICALS BISPHENOL-A (BPA): LITERATURE REVIEW - Marshella Yuanda; Tsabita, Sabrine; Adzroo Atiiqooh Nur Nabiila; Evita Mutiara (Jurnal Kedokteran dan Kesehatan : Publikasi Ilmiah Fakultas Kedokteran Universitas Sriwijaya, 2025)
Bisphenol-A (BPA) is a synthetic chemical widely used in the production of polycarbonate plastics and epoxy resins. BPA is classified as an endocrine-disrupting chemical (EDC) that can cause various adverse effects on human health. Biomonitoring studies in the United States, Germany, and Canada have shown that over 90% of the population have detectable levels of BPA in urine samples. This indicates widespread and sustained exposure in the general population. Furthermore, these findings underscore the importance of implementing preventive measures to mitigate the long-term health risks associated with BPA exposure. This article aims to review the literature on various preventive strategies to reduce health risks associated with BPA exposure. The method employed is a literature review, drawing references from Google Scholar, ScienceDirect, and PubMed databases, encompassing publications from 2020 to 2025. The study results indicate that preventive measures can be implemented through public education, strengthening regulations and policies, promoting lifestyle changes, and utilising antioxidants. Effective prevention requires cross-sectoral collaboration involving individual actions, strong public policies, continuous education, and an integrated scientific approach to create a safer and healthier environment free from BPA hazards.